2010
DOI: 10.1007/s11136-010-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of integrated yoga on quality of life and interpersonal relationship of pregnant women

Abstract: The integrated yoga is an efficacious means of improving the quality of life of pregnant women and enhancing certain aspects of their interpersonal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 24 publications
3
85
0
4
Order By: Relevance
“…Previous studies have investigated the effects of acupuncture (Betts et al, 2012;Borup et al, 2009), homeopathy (Hochstrasser and Mattmann, 1994), Ayurveda (Jayashree, 2008), yoga (Narendran et al, 2005b;Rakhshani et al, 2010), and Qigong (Zhou and Lian, 1989) during pregnancy (Bishop et al, 2011;Kalder et al, 2011;Steel and Adams, 2011). Such interventions have been shown to be effective in reducing occurrences of hypertensive disorders of pregnancy (Hofmeyr et al, 2010;Zhou and Lian, 1989), preventing preterm deliveries (Hochstrasser and Mattmann, 1994;Imdad et al, 2011;Sibai, 2011), improving fetal outcomes (Hochstrasser and Mattmann, 1994;Sabour et al, 2006), and enhance quality of life (Rakhshani, 2013;Rakhshani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the effects of acupuncture (Betts et al, 2012;Borup et al, 2009), homeopathy (Hochstrasser and Mattmann, 1994), Ayurveda (Jayashree, 2008), yoga (Narendran et al, 2005b;Rakhshani et al, 2010), and Qigong (Zhou and Lian, 1989) during pregnancy (Bishop et al, 2011;Kalder et al, 2011;Steel and Adams, 2011). Such interventions have been shown to be effective in reducing occurrences of hypertensive disorders of pregnancy (Hofmeyr et al, 2010;Zhou and Lian, 1989), preventing preterm deliveries (Hochstrasser and Mattmann, 1994;Imdad et al, 2011;Sibai, 2011), improving fetal outcomes (Hochstrasser and Mattmann, 1994;Sabour et al, 2006), and enhance quality of life (Rakhshani, 2013;Rakhshani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions have been shown to be effective in reducing occurrences of hypertensive disorders of pregnancy (Hofmeyr et al, 2010;Zhou and Lian, 1989), preventing preterm deliveries (Hochstrasser and Mattmann, 1994;Imdad et al, 2011;Sibai, 2011), improving fetal outcomes (Hochstrasser and Mattmann, 1994;Sabour et al, 2006), and enhance quality of life (Rakhshani, 2013;Rakhshani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In one study yoga improved subjective wellbeing, mental health and executive functioning within prison populations [13]. Yoga improved the quality of life of pregnant women in various studies and enhanced their interpersonal relationships [14]. Studies over the past 15 years have shown that yoga can improve psychological health during breast cancer treatment [15], as well as health-related quality of life in antipsychotic-stabilized patients [16].…”
Section: Studies Of Yoga's Effects On Quality Of Life and Depressionmentioning
confidence: 99%
“…Health-related quality of life progressively decreases when the probability of being a psychiatric case increases [23]. The physical exercise provided at childbirth education classes, similarly to Yoga classes for pregnant women, bring positive results by improving efficiency and well-being [24,25]. It was observed in both cases that the level of psychological distress decreased and the quality of life in physical, psychological and sociological aspects increased and even the quality of sleep improved among the women participating in childbirth education classes in comparison with control groups.…”
Section: Discussionmentioning
confidence: 99%